Comprehensive analysis of the oral microbiota and metabolome change in patients of burning mouth syndrome with psychiatric symptoms - Shihong Luo; Fangzhi Lou; Li Yan; Yunmei Dong; Yingying Zhang; Yang Liu; Ping Ji; Xin Jin (Journal of Oral Microbiology)
Background Burning mouth syndrome (BMS) is a chronic idiopathic facial pain with intraoral burning or dysesthesia. BMS patients regularly suffer from anxiety/depression, and the association of psychiatric symptoms with BMS has received considerable attention in recent years. The aims of this study were to investigate the potential interplay between psychiatric symptoms and BMS.Methods Using 16S rRNA sequencing and liquid chromatography-mass spectrometry (LC/MS) to evaluate the oral microbiota and saliva metabolism of 40 BMS patients [including 29 BMS patients with depression or anxiety symptoms (DBMS)] and 40 age matched healthy control (HC).Results The oral microbiota composition in BMS exhibited no significant differences from HC, although DBMS manifested decreased α-diversity relative to HC. Noteworthy was the discernible elevation in the abundance of proinflammatory microorganisms within the oral microbiome of individuals with DBMS. Parallel findings in LC/MS analyses revealed discernible disparities in metabolites between DBMS and HC groups. Principal differential metabolites were notably enriched in amino acid metabolism and lipid metabolism, exhibiting associations with infectious and immunological diseases. Furthermore, the integrated analysis underscores a definitive association between the oral microbiome and metabolism in DBMS.Conclusions This study suggests possible future modalities for better understanding the pathogenesis and personalized treatment plans of BMS.